Polymerase gene mutation pattern in patients of chronic Hepatitis B treatment in Prof. Dr. W.Z. Johannes Hospital, Kupang, Indonesia - AGUSTINA WELHELMINA DJUMA; SHERLY DEWU; NORMA TIKU KAMBUNO; AYORINCE BANUNU; OTTO SAHAT MARTUA SILAEN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Djuma AW, Dewu S, Kambuno NT, Banunu A, Silaen OSM. 2024. Polymerase gene mutation pattern in patients of chronic Hepatitis B treatment in Prof. Dr. W.Z. Johannes Hospital, Kupang, Indonesia. Biodiversitas 25: 150-155. Hepatitis B virus (HBV) infection is a significant global health concern, impacting over two billion people worldwide. Among them, more than 240 million individuals develop chronic HBV infection, placing them at a high risk of developing severe liver conditions such as cirrhosis, liver failure, and Hepatocellular Carcinoma (HCC). In 2013, Nusa Tenggara Timur (NTT) emerged as one of the Indonesian provinces with a high incidence of hepatitis cases. Long-term therapy has proven effective in halting disease progression but may also lead to the emergence of resistant mutations. This study aims to analyze mutation patterns in the Polymerase (P) gene as indicators of viral resistance to nucleotide analogs (NUCs) in HBV patients at RSUD Prof. Dr. W.Z. Johannes Kupang, a previously unreported case. The research was conducted at the Hematology-Oncology Medical Laboratory Division, Faculty of Medicine, Universitas Indonesia, RS. Dr. Cipto Mangunkusumo, Department of Internal Medicine, Jakarta. A total of 28 individual samples with positive Hepatitis B surface Antigen (HBsAg) were subjected to PCR sequencing, resulting in 23 positive samples. Mutation profiles were analyzed by comparing them with the reference sequence M54923. Sequencing of the Polymerase (P) gene region was successfully carried out for 14 samples. Among these, 12 (85.71%) exhibited nucleotide substitutions, while the remaining two (9.14%) did not show any mutations. The most prevalent substitution patterns in the P gene included rtQ228H, rtS127R, rtM135L, rtV243I, rtL257A, rtS127A, rtK323N, rtL326R, rtV214I, rtT312S, rtV281E, rtF290Y, rtM299I, rtQ306H, and rtK308N. No mutations associated with antiviral resistance were detected. The use of NUCs in chronic hepatitis B treatment is considered safe for patients at Prof. Dr. W.Z. Johannes Kupang Hospital.